Partnership, Perspectives and Professional Development: A Comparative Exploration of Policy and Practice Within a Shared-Vision of School Placement - Casey, Elva (Trinity College Dublin. School of Education. Discipline of Education, 2025)
Central to Initial Teacher Education programmes in Ireland is the Teaching Council requirement for all Student Teachers to engage in school-based practice, commonly described as School Placement. The Teaching Council presents Initial Teacher Education and School Placement as a first professional step for Student Teachers, whereby they are welcomed into the teaching community, have opportunities to reflect on teacher identity and become socialised into the profession (TC, 2020a). Furthermore, the Teaching Council presents a partnership approach to School Placement as one that is mutually enriching for school communities, Higher Education Institutions and Student Teachers. In this research I probed and compared the interpretations and experiences of partnership in School Placement by partners across the spectrum of teacher education: Student Teachers, School Placement Tutors, Academic Faculty, School Principals, Co-operating Teachers and Newly Qualified Teachers. I did so within the context of teacher education at primary school level. I sought to deepen my understanding, as a professional working in this space, of how partners contribute to School Placement and interpret the contributions of others. Additionally, I aimed to identify whether there exists a fit for purpose system in the Republic of Ireland (hereafter referred to as ‘Ireland’) to facilitate their roles as partners. Furthermore, I sought to develop through this comparative exploration an alternative and well-scaffolded approach to the process of bringing members of the education community together for the purposes of School Placement. My research hopefully opens the gateways to enable educators working in this space to acknowledge and identify existing flaws in the partnership model and to start to address them at a system level which facilitates input at different points and for varying purposes. This research explored the experiences of partnership through School Placement in initialising a career long continuum of professional development for educators at primary school level. The 3 Ps of Partnership, Perspectives and Professionalism/Professional Development in SP functioned as a tripartite framework, guided by linking the research questions to the Teaching Council’s 3 pillars of Innovation, Integration and Improvement (TC, 2021a). In doing so, the research explored the ill-defined and variously interpreted shared- vision of School Placement as a partnership-based first step in the continuum of professional development. Policies and guidelines on School Placement present a slowly evolving ideal of a partnership model through a shared-vision (TC, 2020a, TC 2021a). However, it has been my lived professional experience that the reality on the ground has remained resolutely unchanged for many years. Within the context of Ireland, the practice of School Placement saw its most rapid and unprecedented change recently, when modifications were forced at an accelerated speed by the restraints on site-based experiences imposed during and by the COVID pandemic. As an overarching premise, this research explored how fit for purpose the partnership model of School Placement currently is, post COVID adaptions, as a mode of preparing Student Teachers for the challenges they will face in their early professional lives as Newly Qualified Teachers in a rapidly changing social context and as a first step in their continuing professional development. In throwing the spotlight on the experience of School Placement rather than the assessment of it, the research is situated within the potentially fractious spaces of the dichotomy between the Teaching Council vision of School Placement and the perceptions and lived experiences of the partners themselves. A pragmatic, interpretivist approach was employed, guided by a social constructivist framework. An Iterative Thematic Inquiry approach to the process of review and engagement with initial themes, supported a highly reflexive level of engagement with the emerging themes. The data generated from questionnaires, focus groups, reflective accounts and semi-structured interviews was analysed primarily through narrative analysis and the development of a series of vignettes; thus preserving and focusing on the voices of the participants. This multi-layered research approach enabled me to actively acknowledge and plan for my role as an insider within the research space and the impact that role had on my interactions with the participants and interpretations of the data generated. Four overarching themes emerged from the research: 1) the lack of clarity and agreement on the fulfilment of roles and responsibilities in School Placement, inclusive of a mis-understanding and distrust of the roles of others 2) the unfulfilled potential for School Placement to support developing professionalism and the impact of a continuum approach to professional development 3) the role of School Placement in enabling and supporting reflective practice and career decisions and finally 4) the lack of creativity and diversity in the facilitation of different aspects of School Placement. The findings indicated a need for a more embedded and systematic partnership framework if partnership is to be pursued as the route for facilitating School Placement going forward. I have proposed a staged framework, including the establishment of a Code of Conduct for Partners, a Community of Practice, the development of a Partnership Network, the creation of a Mentor and Professional Development Programme and a Review and Implementation Plan. To support this, a lexicon of common language for Partnership in School Placement should be established. A scheme of accountability to address power imbalances and how to ‘be’ a good partner and be verified as such will also be of value. A coherent improvement agenda focusing on the ideal of a shared-vision is proposed in my conclusion. This would hold the potential to result in a structured partnership framework with reciprocal gain to all partners.
APPROVED